(untitled) (Globalization and Business, 2023)
The correct professional orientation is related to the problems of the society,which are quite difficult to solve. These problems include high rate of unemployment, low labor productivity, career advancement opportunities, etc. There- fore, the purpose of the present paper is to study the factors which affect the professional orientation of young people in Georgia and to determine how much they affect the decision about professional orientation. Graduate students of Georgian secondary schools par- ticipated in the present research. With the help of a special questionnaire, the schoolchildren have expressed their opinions and assessments regarding the factors affecting their pro- fessional choices. Research showed that professional orientation of the most people participating in the research is affected by the following factors: the prestige of a profession, future employment opportunities, the estimated level of income by profes- sion, personal interests and direct relation of family members with the profession. The choice of profession by young people is largely influenced by their parents, while schools fail to provide proper assistance regarding professional orientation. For ensuring representativeness of the research results, the research limitations were identified. In particular, public and private, regional and central secondary education institutions of Georgia involved in the research were previously determined by territorial and ownership forms. The research was conducted based on a structured survey format through preliminary developed questionnaires. The questionnaire was completely filled out by 712 respondents from all around Georgia. In our opinion, taking the current limitations into consideration ensures representativeness of the research results. Identification of the factors affecting professional orientation in Georgia provides possibility to consider these factors while planning the activities of proper professional orientation. Wrong professional orientation of young people is relat- ed to a number of negative consequences. Youth support in professional orientation should be based on the study of the factors affecting the choice of future profession. Until now, in Georgia there were only assumptions about the factors con- sidered by young people when choosing the profession. The purpose of the presented study is to find out which factors affect the professional orientation of young people in Georgia on a scientific basis. The analysis of the research results showed that professional orientation of young people in Georgia is affected by the following factors: prestige of a profession, possibility of future employment, estimated level of income to be received by profession, personal interests, academic performance at school and direct relation of family members with the profession. It should be noted that the factors affecting professional orientation revealed by the research, in turn, directly affect the level of motivation of individuals to study in higher education institutions and significantly determine the intensity of academic mobility processes, which also requires further researches. Based on the research, the following conclusions can be made regarding the factors affecting professional orientation of young people in Georgia: When choosing a profession most of the 12th-grade students of secondary schools pay special attention to prestige of a profession, possibility of future employment, estimated level of income by profession, personal interests, academic performance at school and direct relation of family members with the profession. The respondents consider that perspective of employment in chosen profession is the most important among the other factors, which can be positively evaluated from the perspective of making correct professional choice. However, the fact that most of the respondents consider that protection by friends and relatives is the main factor for being employed in chosen profession is an extremely negative factor for making correct professional choice. Such opinion can be considered as one of the main reasons of wrong professional orientation. In addition, the existence of the factor of protectionism in employment possibilities can be considered as one of the main reasons of low motivation of learning at higher education institutions. Being informed about labor market is essential for correct professional orientation of young people. The research substantiates that even according to the respondents’ evaluation, their level of awareness of labor market in not sufficient. However, it is likely that the real level of their awareness of la- bor market is even lower. The empirical results of the research showed that the better an individual is informed about the chosen profession, the less likely he/she is to change his/her choice of profession. An important part of the graduate students of secondary schools find it easy tochoose a profession, they make decisions easily and spend very little time on making a decision on future profession; as a result, young people are not sure about the correctness of their professional choice. Empirical studies also showed that the probability that the individual is absolutely convinced in his professional choice and is not going to change it is about 20%, which is quite a low indicator. Parents play an important role in making decisions on future professions by their children, while the involvement and support of schools (teachers) in correct professional orientation of young people is very low; Family income considerably affects professional orientation of young people in Georgia as young people from lowincome families are forced to focus on statefunded specialties rather than on their own professional interest; Study of one’s own personal characteristics is quitean important factor. In particular, the better the individual has studied his/her personal characteristics, the more confident he/she is in the decision about the future profession.